Alcohol Consumption, Progression of Disease and Other Comorbidities, and Responses to Antiretroviral Medication in People Living with HIV - Manuela G. Neuman; Michelle Schneider; Radu M. Nanau; Charles Parry (AIDS Research and Treatment)
The present paper describes the possible connection between alcohol consumption and adherence to medicine used to treat human deficiency viral (HIV) infection. Highly active antiretroviral therapy (HAART) has a positive influence on longevity in patients with HIV, substantially reducing morbidity and mortality, including resource-poor settings such as South Africa. However, in a systematic comparison of HAART outcomes between low-income and high-income countries in the treatment of HIV-patients, mortality was higher in resource-poor settings. Specifically, in South Africa, patients often suffer from concomitant tuberculosis and other infections that may contribute to these results. Alcohol influences the use of medicine for opportunistic infections (e.g., pneumonia, tuberculosis), or coinfections HIV-hepatitis viruses-B (HBV) and C (HCV), cytomegalovirus, or herpes simplex virus. Furthermore, alcohol use may negatively impact on medication adherence contributing to HIV progression. The materials used provide a data-supported approach. They are based on analysis of published (2006–2011) world literature and the experience of the authors in the specified topic. Intended for use by health care professionals, these recommendations suggest approaches to the therapeutic and preventive aspects of care. Our intention was to fully characterize the quality of evidence supporting recommendations, which are reflecting benefit versus risk, and assessing strength or certainty.